'They're getting a taste of our world': A qualitative study of people with multiple sclerosis' experiences of accessing health care during the COVID‐19 pandemic in the Australian Capital Territory. (6th July 2021) - Parkinson, Anne; Drew, Janet; Hall Dykgraaf, Sally; Fanning, Vanessa; Chisholm, Katrina; Elisha, Mark; Lueck, Christian; Phillips, Christine; Desborough, Jane
Abstract: Background: People with multiple sclerosis (MS), who are often immunocompromised, require complex care and engage with a variety of health‐care providers to manage their health. Objective: To elucidate people with MS' experiences of accessing health care during the COVID‐19 pandemic in Australia. Design: A qualitative study involving semi‐structured interviews and thematic analysis. Settings and participants: Eight adults with a clinical diagnosis of MS participated in telephone or video call interviews between June and July 2020. Results: Participants were aware that having MS made them more vulnerable to contracting COVID‐19. In some cases, usual care was postponed or not sought. Some circumstances warranted the risk of a face‐to‐face consultation. Benefits of telehealth consultations included improved access, convenience and being contact‐free. In comparison with video consultations, those via telephone were considered less personal and limited capacity to read body language, and for physical examination. Most participants hoped to incorporate telehealth into their future health‐care routines. Discussion and conclusion: Personal risk assessment and trust in health‐care professionals are determinants of the mode through which people with MS accessed health care during the COVID‐19 pandemic. Telehealth has been a valuable tool to mitigate COVID‐19 transmission through enabling contact‐free consultations. People with MS may find specific value in video consultations, which enable visualization of physical function. There is a need for training and support for all clinicians to conduct remote consultations. Patient or public contribution: This study was conducted by a team comprised of four people with MS, a neurologist and four health services researchers.